Measure and integration on non-locally compact spaces and representation theory - Waller, Raven (2019)
The problem of studying representations of algebraic groups over higher dimensional local fields has already attracted a lot of attention. While many of the advances in this area involve very technical machinery and produce highly abstract results, in this thesis we approach this problem from a much more explicit angle, where we encounter phenomena which do not present themselves in the earlier approaches.